Prototipe Metadata Pada Data Warehouse Untuk Basis Data Heterogen - Stefany Yunita Bara'langi (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2014)
This research aims to design a prototype for data warehouse as a data storage that has a structure and derived from different data sources (heterogeneous). Metadata is the data description which can be used as a catalog so that users can get complete information about the database is built. Data warehouse is a collection of data that are subject-oriented, integrated, time variant and non-volatile . These properties make the data warehouse included in OLAP (OnLine Analytical Proceesing) where the data stored and can not be changed at any time (real time). That was the distinguishes between a regular information system. The ability of data warehouses is extraction data from heterogeneous databases. Heterogeneous database is the database that is derived from several different data sources and have different table structures also vary. The author designed a prototype with the ETL (Extract, Transform, Load) and using a star schema. The design of data warehouse was used Kimball method which designed from branch table to centralized (bottom-up approach). The prototype of this metadata can help the decision-making process with the use of data mining techniques.